2018
DOI: 10.1155/2018/8543763
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathogenesis of Nonalcoholic Steatohepatitis- (NASH-) Related Hepatocellular Carcinoma

Abstract: The proportion of obese or diabetic population has been anticipated to increase in the upcoming decades, which rises the prevalence of nonalcoholic fatty liver disease (NAFLD) and its progression to nonalcoholic steatohepatitis (NASH). Recent evidence indicates that NASH is the main cause of chronic liver diseases and it is an important risk factor for development of hepatocellular carcinoma (HCC). Although the literature addressing NASH-HCC is growing rapidly, limited data is available about the etiology of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
129
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(130 citation statements)
references
References 91 publications
(90 reference statements)
0
129
0
1
Order By: Relevance
“…As for hepatitis viral infection, a chronic increase in ROS promotes the initiation and progression of non-alcoholic fatty liver disease to non-alcoholic steatohepatitis and then to HCC [ 88 , 89 ]. Increased production of ROS is caused by an accumulation of excess lipid in cytoplasmic lipid droplets in hepatocytes [ 88 , 89 ]. Several Ca 2+ channels, transporters and binding proteins are thought to be important in the initiation and progression of HCC ( Table 5 ).…”
Section: Store-operated Ca 2+ Entry Serca2b Amentioning
confidence: 99%
“…As for hepatitis viral infection, a chronic increase in ROS promotes the initiation and progression of non-alcoholic fatty liver disease to non-alcoholic steatohepatitis and then to HCC [ 88 , 89 ]. Increased production of ROS is caused by an accumulation of excess lipid in cytoplasmic lipid droplets in hepatocytes [ 88 , 89 ]. Several Ca 2+ channels, transporters and binding proteins are thought to be important in the initiation and progression of HCC ( Table 5 ).…”
Section: Store-operated Ca 2+ Entry Serca2b Amentioning
confidence: 99%
“…Here, activation of oncogenic mechanisms is via genetic, metabolic, immunologic, and endocrine pathways. 117 The development of hepatic inflammation and fibrosis is affected by deregulated activation of nuclear factor-kappa B (NF-κB). While chronic activation of NF-κB increases the production of tumor necrosis factor (TNF) and HCC development, 118 there is also overexpression of miR-21 in mouse models of NASH which promotes HCC growth and migration of HCC cell lines.…”
Section: Pathogenesis Of Hepatocellular Carcinomamentioning
confidence: 99%
“… 17 This increased lipid content of hepatocytes may not only cause an increase in the oxidative stress, but also results in increased β-oxidation of free fatty acids in mitochondria, leading to formation for reactive oxygen species, further causing lipid peroxidation, and continuing the cascade as increased secretion of pro-inflammatory cytokines, hepatocyte damage, inflammation, apoptosis and fibrosis. 18 , 19 In fact, this basic ‘hepatic steatosis’ scheme remains a key component of the multiple parallel-hit hypothesis. Excessive calorie intake by unhealthy diet options and sedentary lifestyle are the examples of environmental factors contributing to fatty liver.…”
Section: Mechanisms and Effects Of Hepatic Steatosismentioning
confidence: 99%
“…Studies have demonstrated that ingestion of high-fat diet results in impairment of intestinal barrier function. 18 , 23 This can lead to the leakage of bacterial products, most importantly lipopolysaccharides, to the bloodstream. These molecules have been found to play a role in the development of hepatic steatosis and inflammation through toll-like receptors.…”
Section: Mechanisms and Effects Of Hepatic Steatosismentioning
confidence: 99%
See 1 more Smart Citation